Smart Cities and Sustainability in Central-Eastern Europe - Szendi, Dóra (Theory, Methodology, Practice – Review of Business and Management, 2023)
Accelerating globalisation is setting economies serious challenges. Rapidly changing conditions (globalisation, industry 4.0, sustainability or pandemics) demand innovative solutions from regions. The way in which regions with different levels of development respond to external shocks can have a major impact on (and increase) existing socio-economic disparities between regions worldwide. Central and Eastern Europe is particularly vulnerable in this respect, as a peripheral region, where the impact of various crises is greater due to less diversified economies and lower income levels. The aim of this study is to examine the territorial differences in Central-Eastern Europe and to analyse the situation of smart cities as a potential alternative in the region. The results show that the region's capitals are in the second half of the European ranking in terms of both smart cities and sustainable development, forming a broadly defined Polish-Czech-Slovak and Hungarian-Romanian-Bulgarian capital cluster. The comparison of the components of the sustainability index revealed that cities in the CEEC region are in a less favourable position in the dimensions measuring mostly “hard” indicators (innovation, industry, infrastructure) than in the components measuring more “soft” elements, and the opinion of the inhabitants is diverse about the cities’ sustainable performance.